Genome‐wide association study confirms that the chromosome Z harbours a region responsible for rumplessness in Hongshan chickens. (19th April 2018) - Wang, Q.; Pi, J.; Shen, J.; Pan, A.; Qu, L.
Summary: Rumplessness in Hongshan chickens has been reported as a novel sex‐linked characteristic. Re‐sequencing data suggest that a pseudogene on the Z chromosome, LOC431648, is affiliated with this phenotype. In this study, we chose 23 rumpless and 25 normal Hongshan chickens to localize the potential variation by means of a genome‐wide association study using a high density microarray. A region on the Z chromosome was found to be closely associated with rumplessness in Hongshan chickens. The region, located in gene LINGO2, was approximately 3 Mb away from pseudogene LOC431648 . The function of this gene has not yet been studied in birds. Differential expression of the candidate genes in the tail feather follicles was not detected by q‐PCR, which suggests that the rumplessness trait could be attributed to other genetic mechanisms.